Implementing Application of Powtoon-Based Learning Media Problem Based Learning to Improve Student Learning Outcomes - Hasanah, Hasanah; Nurmairina, Nurmairina; Nurlaili, Nurlaili; Lestari, Nila; Yarshal, Dinda (Teunuleh Publisher, 2024)
The purpose of this research is to analyze the application of Powtoon-based problem-based learning to improve the learning outcomes of third-grade students at SD IT Darussalam. This research is a Classroom Action Research. The subjects in this research were all third-grade students at SD IT Darussalam, totaling 34 students, consisting of 18 boys and 16 girls. The instruments used were observation sheets for learning implementation and learning outcome tests. The data analysis technique used was descriptive data analysis. The learning process after implementing Powtoon-based problem-based learning showed a significant increase. In the first cycle, the first meeting, 41.17% of students successfully completed the learning. In the first cycle, the second meeting, the number of students who successfully completed the learning increased to 67.63%. Continuing to the second cycle, the first meeting, the number of students who successfully completed the learning increased to 82.35%. This has not yet reached the expected learning outcomes, so improvements were made in the second cycle, the second meeting, and it was obtained that 88.23% of students successfully completed the learning. The students' classical learning achievement has been achieved because 88.23% ? 80%, so there is no need to conduct further cycles. It can be concluded that the application of Powtoon-based problem-based learning has proven to be effective in improving the learning outcomes of third-grade students at SD IT Darussalam, and the action hypothesis is accepted.